Immediate Dental Implants Enriched with L-PRF in the Esthetic Zone - Manoti Sehgal; Lovleen Puri; Sapna Yadav; Puja Malhotra; Sumit Singh Phukela; Bhupender Yadav; Bharti Raina (Case Reports in Dentistry)
The aim of this article is to present the clinical application of immediate implant placement with L-PRF and immediate prosthetic loading in anterior esthetic region. A 24-year-old healthy female patient reported with a chief complaint of poor esthetics in the upper front tooth region with retained deciduous teeth. On oral examination, there were retained deciduous teeth (52, 53, and 63) with congenitally missing permanent successors. The retained deciduous teeth were extracted, and immediate implant placement was done in the extraction sockets along with L-PRF membranes in one surgical session under local anesthesia. Immediate temporization was performed with composite crowns on immediately placed dental implants. After 3 months of the healing period, the final implant-level impressions were made and the temporary composite crowns were replaced with the final zirconia porcelain crowns. A 12-month follow-up was made, and satisfactory esthetic and functional results were obtained.